Frost injury in wheat: preliminary variety evaluation - Scheeren, Pedro Luiz (Pesquisa Agropecuaria Brasileira, 2014)
The grain setting (flower fertility) of 31 wheat genotypes (Triticum aestivum L.), exposed to frost, at three growth stages, was evaluated. It was observed: a) less frost injury during booting stage than at heading stage; b) there was no seed setting in plants injured by frost during anthesis; c) there was genetic variability among genotypes at the same growth stage, regarding their reaction to frost; and d) the behavior of a given genotype at different growth stages was also variable.